New Zealand's Food System Is Unsustainable: A Survey of the Divergent Attitudes of Agriculture, Environment, and Health Sector Professionals Towards Eating Guidelines - Jones, Rebekah; Wham, Carol; Burlingame, Barbara (Frontiers in Nutrition, 2019)
Background: The Food and Agriculture Organisation has called for sustainable diets, which align with SDG 2, Zero Hunger, and SDG 12, Sustainable Consumption and Production. The inclusion of sustainability characteristics in New Zealand's (NZ) eating and activity guidelines (EAGs) may lead to achieving sustainable diets. This study aimed to evaluate the agreement among sectoral professionals of including sustainability characteristics within the guidelines. Methods: Agriculture, environment, and health sector professionals were invited to complete an online survey to establish agreement with sustainability characteristics and sustainability statements. Opinion and attitude questions were completed using a 5-item Likert scale. One-way ANOVA analyses were conducted to compare the level of agreement and differences in means of the sector levels of agreement whilst controlling for covariates. Post-hoc tests were used to determine sectoral differences. Results: Overall, 298 (65% female) respondents completed the survey from the agriculture (37%), environment (22%), and health (41%) sectors. Two-thirds (66%) of respondents were over 35 years and 90% had a tertiary education. Two-thirds (63%) of respondents disagreed that NZ's current food system is sustainable; health (77%) and environment (78%) sector respondents had greater disagreement than those from agriculture (35%; P = 0.00). Overall, 77% of respondents agreed that sustainability characteristics should be included in guidelines; health (90%) and environment (84%) sector respondents had greater agreement than from agriculture (58%; P = 0.00). Five sustainability characteristics received high levels of agreement (>90%) for inclusion: dietary diversity, sustainable seafood, limit processed foods, reduced food waste, and sustainable lifestyle behaviours. Agreement for eight sustainability characteristics was highest among the health and environment sectors vs. the agricultural sector (P < 0.05). A relatively low level of agreement was received from all three sectors, particularly the environmental sector (68.7%), towards the characteristic “to consume recommended serves of dairy products.” Only 38.5% of all respondents agreed with the inclusion of “organic food produce.” Negative associations were observed between respondents' opinions regarding the sustainability of NZ's current food system and familiarity with the EAGs. Conclusion: Professionals from the agriculture, environment, and health sectors largely support the inclusion of sustainability characteristics in NZ's EAGs. A multi-sectoral approach will be required to address areas of divergence.